Tensile bond strength of fiberglass and anatomized posts - Herbert Cosio Dueñas; Irma Soledad Vilavila Huarancca; Liceth Lazo Otazú; Danitza Garate Villasante (Revista Cubana de Estomatología, 2021)
Introduction: Fiberglass posts often fall off their position due to loss of adhesive capacity when they are subjected to masticatory force.